Efficient Image Encryption Scheme Based on the Moduli Set {2n - 1, 2n, 2n +1} - Saheed, Y. K.; Gbolagade, K. A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2026)
This paper presents an image encryption scheme that utilizes three moduli set. The proposed scheme is based on three moduli set {2n-1, 2n, 2n+1}, which is efficient, required little hardware, and did not diminish the Residue Number System dynamic range. Also, it promises high speed, reduces area, decreases internal delay conversion from Residue Number System (RNS) to binary. This is because in the reverse converter, the computation of the multiplicative inverse is removed and it achieves low-power very large scale integration implementation for image processing such as digital image filtering. The end results of the RNS image encoder in this new scheme are in small-word length and are arranged in a certain encrypted order. A Residue-Binary converter (decoder) is used to recover the plain image. The proposed scheme is simulated on an image using matrix laboratory tool. An attacker who breaks into network does not know the moduli set and the order of the encrypted bit stream that are computed in parallel. The scheme can be applied to any image formats as against the best known state-of-theart.